2016
DOI: 10.1175/jas-d-16-0108.1
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Mesoscale Winds in the Upper Troposphere and Lower Stratosphere

Abstract: Spectral analysis is applied to infer the dynamics of mesoscale winds from aircraft observations in the upper troposphere and lower stratosphere. Two datasets are analyzed: one collected aboard commercial aircraft and one collected using a dedicated research aircraft. A recently developed wave-vortex decomposition is used to test the observations' consistency with linear inertia-gravity wave dynamics. The decomposition method is shown to be robust in the vicinity of the tropopause if flight tracks vary suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 29 publications
3
54
0
Order By: Relevance
“…Further work remains to be done, for instance, to illuminate the nature of the divergence-dominated regime and to test for seasonal variations [e.g., Callies et al, 2015]. But the results of the present study shows that drifters can be used to deduce important aspects of the turbulent dynamics at lateral scales far below those sampled with most other instruments.…”
Section: Summary and Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Further work remains to be done, for instance, to illuminate the nature of the divergence-dominated regime and to test for seasonal variations [e.g., Callies et al, 2015]. But the results of the present study shows that drifters can be used to deduce important aspects of the turbulent dynamics at lateral scales far below those sampled with most other instruments.…”
Section: Summary and Discussionmentioning
confidence: 80%
“…The results are reminiscent of those from the upper troposphere, where there is an enstrophy cascade from 2000 km down to several hundred kilometers and a transition to a shallower kinetic energy spectrum where R o ≈1 [ Nastrom and Gage , ]. Callies et al [] and Callies et al [] used the MOZAIC (Measurement of OZone and water vapour by AIrbus in‐service airCraft) data to show that the rotational energy spectrum dominates at the large scales near the tropopause, while the rotational and divergent components are nearly equal at the small scales. Structure functions, calculated with the same data, also show equal contributions at small scales, at least in the lower stratosphere, and a weaker divergent component in the upper troposphere across all scales [ Lindborg , ].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This is the shallow, mesoscale part of the celebrated Nastrom & Gage (1985) spectrum, which is traditionally interpreted as a k −5/3 h spectrum but is also consistent with k −2 h . There is ongoing debate about the nature of this part of the spectrum: Callies et al (2014Callies et al ( , 2016 attribute it to nearly linear IGWs on the basis of their separation between IGWs and geostrophic motion, but this interpretation is controversial (see Li & Linborg (2018) for a recent critique). Callies et al (2016) note that 'the wave interpretation is .…”
Section: Forced Response and Observed Ocean And Atmosphere Spectramentioning
confidence: 99%
“…Our results are relevant to important open questions about the nature of submesoscale motion in the ocean and mesoscale motion in the atmosphere. Recent data analyses by Bühler et al (2014) and Callies et al (2014Callies et al ( , 2016 led them to hypothesise these motions are dominated by almost linear IGWs. The prediction of a k −2 spectrum lends support to this hypothesis by identifying a robust mechanism -diffusion by turbulence -that produces a spectrum consistent with observations (see §4).…”
Section: Introductionmentioning
confidence: 99%
“…Measurements using different techniques, i.e., radiosondes, aircraft, and radars, have shown that power spectra of horizontal velocities as a function of frequency (or wavenumber) generally follow a f −5/3 (or k −5/3 ) power law (where f refers to frequency and k to wavenumber) (e.g., Gage, 1979;Basley and Carter, 1982;Larsen et al, 1986), although deviations from this slope have also been observed such that a −5/3 power law can not be assumed to be universal (e.g., Larsen et al, 1982). Even after three decades of study, the mechanisms producing the −5/3 spectrum in the mesoscale regime remain to be controversial (e.g., Gage, 1979;Gage and Nastrom, 1990;Larsen et al, 1982;Lilly, 1983;Vallis et al, 1997;Koshyk et al, 1999;Tung andOrlando, 2003, 2004;Smith, 2004;Lindborg, 2006;Brune and Becker, 2013;Callies et al, 2016;Bierdel et al, 2016, and many others). One of the explanations is that the mesoscale spectrum is the production of inertia-gravity waves (e.g., VanZandt, 1982;Dewan, 1997), which is similar to the classical Garrett-Munk spectrum found in the ocean (Garrett and Munk, 1975).…”
Section: Introductionmentioning
confidence: 99%